A new species of Hoplias malabaricus species complex (Characiformes: Erythrinidae) from the Crepori River, Amazon basin, Brazil - Auzier Guimarães, Karen Larissa (2021)
A new species belonging to the Hoplias malabaricus complex from the Amazon basin, Brazil, is described. The new species is characterized by 15–16 predorsal scales, 37–39 lateral-line scales, 5 scales from dorsal fin to lateral line, 38–39 vertebrae, iii-iv, 7–8 anal-fin rays, ii-iv, 12–15 caudal-fin rays, last vertical series of scales on the base of caudal-fin rays forming a straight line, 6–7 dark bands in anal fin and no distinctive dark bands or blotches on flanks. The new species is also distinguished from other congeners of the H. malabaricus species-group by means of landmark-based morphometrics and DNA Barcoding (Cytochrome c Oxidase I gene). An identification key to species of the H. malabaricus species complex is provided.